The Big-bang Strategy and Non-rational Behavior in the Russian Transitional Economy in the 1990s - Rozmainsky, I.V. (Економічний вісник Донбасу, 2015)
The paper offers the following hypothesis: the Big Band (Shock Therapy) strategy of the 1990s in Russia has led to more non-rational behavior of the ordinary Russian people. The point is that in order to make completely rational decisions a person needs avoid both lack of information and information overload. Radical “transition to the market system” by means of the Big Bang strategy had reinforced both these obstacles to rational behavior. On the one hand, radical reforms had increased uncertainty. On the other hand, due to these reforms ordinary Russian people faced with big amount of information which was complex for perception, first of all, on goods and financial markets. The contemporary social, political and economic problems of Russia are concerned, in particular, with low degree of rationality of many its citizens. Roots of it are, among others, in the Big Bang strategy of the 1990s.